Strategic market decisions : a reader - 4 0 16; Cox, Keith Kohn,;McGinnis, Vern J.; 5 (Englewood Cliffs, New Jersey : Prentice-Hall, Inc., 1982)
Collects articles on corporate strategic planning, management and markets.
Includes bibliographical references.
Young Adult.
Keywords: 2 -- 0; 6; Addresses, essays, lectures.;Management;Addresses, essays, lectures.;Addresses and essays.;Management. -- Marketing;Marketing;Marketing;Marketing; 20; 2